انیسویں اور بیسویں صدی کے ہندوستانی مسلم جدیدیت پسند اور مسئلہ زن - ثمینہ حسنین (FIKR-O NAZAR فکر ونظر, 2012)
Leaving aside the very early maternal societies humanity had not yet become aware of the concepts of personal ownership, rights and duties, and inequality, in every age, especially in the medieval age inequality between man and woman was an accepted fact. Regardless of the Quranic concept of the relations between man and woman, even in the medieval Muslim societies we do not see the condition of women any better.It was in the modern period that the issue of equality of man and woman, women's rights and freedom arose and developed. In the modern Muslim world this issue arose at the time when the West came with its imperialistic and philosophical influences. It was then that the orientalists and missionaries began ridicule the Muslims in many areas, and the matter of equality between man and woman was a key area. In India, especially in the north, Muslim modernists, the representatives of Aligarh school, made this issue a point of focus and discussion in their debates. This paper analyzes this discussion.